2019
DOI: 10.1016/j.heliyon.2019.e02120
|View full text |Cite
|
Sign up to set email alerts
|

Stable isotope compositions of precipitation from Gunnison, Colorado 2007–2016: implications for the climatology of a high-elevation valley

Abstract: Stable isotope ratios of precipitation are useful tracers of climatic and hydrological processes. To better understand the isotope hydro-climatology of a high-elevation Rocky Mountain valley we collected meteoric water samples from Gunnison, Colorado, USA and determined stable isotope values for 239 individual precipitation events over a nine year period. Annual precipitation in Gunnison is moderately bi-modal with significant winter snowfall and convective summer thunderstorms associated with the North Americ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 39 publications
3
11
0
Order By: Relevance
“…Putman et al (2019) found LMWLs are not well defined with less than 4 years of data. We base our LMWL calculation on only 2 years of data, but the large number of observations linearly aligned with a high degree of correlation in the dual isotope space and our LMWL is in agreement with previous sampling campaigns in the region (Marchetti & Marchetti, 2019). The ER LMWL contains a slightly reduced slope in comparison to the GMWL, but when divided into rain and snow illustrates fundamental differences between warm and cold season precipitation.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Putman et al (2019) found LMWLs are not well defined with less than 4 years of data. We base our LMWL calculation on only 2 years of data, but the large number of observations linearly aligned with a high degree of correlation in the dual isotope space and our LMWL is in agreement with previous sampling campaigns in the region (Marchetti & Marchetti, 2019). The ER LMWL contains a slightly reduced slope in comparison to the GMWL, but when divided into rain and snow illustrates fundamental differences between warm and cold season precipitation.…”
Section: Discussionsupporting
confidence: 84%
“…These are common proxies for the Rayleigh distillation effect as storms move inland, and reflect differences between the temperature of the initial cloud condensate in the air mass and the condensation temperature at our sampling site (Beria et al, 2018; Clark & Fritz, 1997; Putman et al, 2017). The slope describing δ 18 O in snow as a function of temperature is 0.6‰ per °C which falls in the range presented by others (Bowen, 2008; Marchetti & Marchetti, 2019) and deemed acceptable.…”
Section: Discussionsupporting
confidence: 71%
“…Precipitation presents an input to groundwater, and therefore knowledge on the isotope composition of precipitation is a prerequisite for groundwater studies. Temporal and spatial patterns of isotopes in precipitation (expressed as δ 2 H and δ 18 O values and the tritium activity concentration, A) have been observed since the 1950s and have contributed to hydrological and hydrogeological research [13][14][15][16], climate and paleoclimate studies [4,15,[17][18][19][20][21][22], and ecological research [23][24][25]; further, precipitation isotope mapping has been widely implemented during recent decades [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Stable isotopes of water for streams, canals, springs, and groundwater were analyzed to help discern the origin and isotopic evolution of streamflow and groundwater recharge in the study area. A plot of δ 18 O compared to δ 2 H in all samples is shown in figure 5 along with a local meteoric water line (LMWL) derived from precipitation samples collected in the headwaters of the Gunnison River (Marchetti and Marchetti, 2019). The sample with the lightest values (δ 2 H = −116, δ 18 O = −15.46) and closest to the LMWL is from the East Canal (site 12), which was sampled during the irrigation season; the sample reflects snowmelt from higher elevations as the source of irrigation water.…”
Section: Stable Water Isotopesmentioning
confidence: 99%
“…Figure 5. Stable isotopic composition of surface water and groundwater in the Sunflower Drain study area, Colorado, during 2017-19, plotted with a local meteoric water line fromMarchetti and Marchetti (2019). (LMWL, local meteoric water line)…”
mentioning
confidence: 99%